2017
DOI: 10.1515/lpts-2017-0031
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Air Gap Change of Low-Speed Generator Considering Thermal Expansion, Centrifugal Force and Magnetic Force Effects

Abstract: The paper provides the data collected over a three-year period to illustrate the dynamic air gap change depending on generation modes of four hydropower generators with similar design. The tests were performed on hydropower units at the rated apparent power of 105 MVA and the air gap of 20 mm. The results obtained showed that the average air gap change in different modes could reach up to 2.1 mm. Around 90 % of air gap change results from thermal expansion and 10 % were determined by centrifugal and magnetic f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
0
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 9 publications
(13 reference statements)
1
2
0
2
Order By: Relevance
“…It was shown that the force of inertia and temperature effects have a critical role for the air gap variation. For Unit 1 in this study the inertia force accounted for only 0.2 mm of the variation, which is less than 0.7 mm quoted in the previous research [5]. Temperature effects accounted for 1.5 mm, which supports the previous conclusions that the thermal expansion effects could cause up to 90 % of the air gap variation.…”
Section: Shaft Displacement Resultssupporting
confidence: 78%
See 2 more Smart Citations
“…It was shown that the force of inertia and temperature effects have a critical role for the air gap variation. For Unit 1 in this study the inertia force accounted for only 0.2 mm of the variation, which is less than 0.7 mm quoted in the previous research [5]. Temperature effects accounted for 1.5 mm, which supports the previous conclusions that the thermal expansion effects could cause up to 90 % of the air gap variation.…”
Section: Shaft Displacement Resultssupporting
confidence: 78%
“…Therefore 2 % is not a critical portion of the variation. The other sources of variation were discussed in the previous publication [5], but the unit studied was of a slightly different design. It was shown that the force of inertia and temperature effects have a critical role for the air gap variation.…”
Section: Shaft Displacement Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Одним из самых опасных дефектов крупных гидрогенераторов (ГГ) является нарушение формы и изменение величины воздушного зазору между ротором и статором [1][2][3]. Такой дефект может привести к серьёзным авариям с задеванием ротора за статор, разрушением обмоток, стали статора и полюсов.…”
Section: Introductionunclassified
“…Появление дефекта вызывается воздействием различных явлений в машине. Согласно [1,2] воздушные зазоры между статором и ротором в гидрогенераторах в диаметрально противоположных точках не должны отличаться друг от друга более чем на 20 % от среднего значения, если инструкциями изготовителя не предусмотрены более жёсткие нормы. Для капсульных ГГ, в которых воздушный зазор составляет всего несколько миллиметров, отклонение зазора от нормируемых значений является особенно опасным.…”
Section: Introductionunclassified